BOOK REVIEW: DEVELOPING COLLABORATIVE LEARNING ENVIRONMENT USING LEARNER-CENTERED STRATEGIES - Nanquil, Luisito Manalansan (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2021)
To be a competent, dynamic, and effective teacher needs a lot of evaluation and reflection. A product of this thought should be learning outcomes that demonstrate mastery, fluency, and achievement of the learners, who are the main focus of teaching and learning. This paper aims to examine the book authored by Rollins by connecting the observations and experiences of the reviewer to the points, theories, and practices tackled by the author in her book. It is the hope of teachers around the globe to offer collaborative learning environment that will cater to the needs and diversities of learners.